1987
DOI: 10.1620/tjem.153.303
|View full text |Cite
|
Sign up to set email alerts
|

Age-related brain atrophy enhanced by smoking: A quantitative study with computed tomography.

Abstract: We examined the chronic effect of smoking on brain atrophy quantitatively with computed tomography (CT). Study was performed on 159 smokers and 194 non-smokers from 40 to 69 years old with neither neurological nor focal abnormality in brain CT. Brain atrophy index (BAT) which was a quantitative marker of brain atrophy reported previously, was calculated from each pixel of brain CT. There was a significant age dependent increase of BAT in both non-smokers and smokers. Smokers showed a significant increase in BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Research using computed tomography showed that cigarette smoking was associated with increased brain atrophy with advancing age (Akiyama et al, 1997;Hayee et al, 2003;Kubota et al, 1987), and a recent MRI study found smaller volumes and lower tissue densities in prefrontal and anterior cingulate cortexes and cerebellum of healthy adult smokers (Brody et al, 2004). Prefrontal cortex density in this study was inversely related to pack-year smoking history.…”
Section: Introductionsupporting
confidence: 49%
“…Research using computed tomography showed that cigarette smoking was associated with increased brain atrophy with advancing age (Akiyama et al, 1997;Hayee et al, 2003;Kubota et al, 1987), and a recent MRI study found smaller volumes and lower tissue densities in prefrontal and anterior cingulate cortexes and cerebellum of healthy adult smokers (Brody et al, 2004). Prefrontal cortex density in this study was inversely related to pack-year smoking history.…”
Section: Introductionsupporting
confidence: 49%
“…Recent brain neuroimaging studies reported structural abnormalities in non-alcoholic chronic smokers. Specifically, MRI indicated smaller neocortical GM volumes and lower densities in the prefrontal cortex, smaller left anterior cingulate volume, and lower GM densities in the right cerebellum of chronic smokers compared to non-smokers (Brody et al, 2004), and computed tomography showed increased generalized brain atrophy with advancing age in chronic smokers (Akiyama et al, 1997;Hayee et al, 2003;Kubota et al, 1987). Volume reductions in these regions are also commonly reported in alcoholism (see Sullivan, 2000, for review).…”
Section: Discussionmentioning
confidence: 99%
“…Early, smaller studies found inconclusive evidence of an association, with one study reporting an association between smoking and higher levels of brain atrophy on CT scan in adults aged 40-69 years (Kubota et al 1987) while another reported no association with silent lacunar infarcts in 270 subjects free of neurological deficits over the age of 40 years (Shintani et al 1998). …”
Section: Silent Brain Infarcts Wmhi Leukoariosis Other Volumetric mentioning
confidence: 99%